2015
DOI: 10.3171/2014.11.jns141269
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of intracerebral hemorrhage among patients with chronic osteomyelitis

Abstract: Stroke, either ischemic stroke or intracerebral hemorrhage (ICH), is the leading cause of disability and one of the leading causes of death in adults. 10,28,31 Patients with ICH are at higher risk of disability than those with ischemic stroke, inclusive of greater economic and health care burdens. Exhibiting in 10%-20% of all strokes, ICH has been associated with both noninfectious and infectious factors. Studies have shown that intravenous drug use-related systemic infections increase the risk of cerebral vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Firstly, COM patients have higher incidences of physical and psychological disabilities [3]. Secondly, recent studies have demonstrated that patients with COM might suffer from increased susceptibility to other accompanying diseases, such as rheumatoid arthritis [4], acute pancreatitis [5], diabetes mellitus [6], and intracerebral hemorrhage [7]. Thirdly, diagnosis, treatment, and rehabilitation of COM bring great socioeconomic burdens [8].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, COM patients have higher incidences of physical and psychological disabilities [3]. Secondly, recent studies have demonstrated that patients with COM might suffer from increased susceptibility to other accompanying diseases, such as rheumatoid arthritis [4], acute pancreatitis [5], diabetes mellitus [6], and intracerebral hemorrhage [7]. Thirdly, diagnosis, treatment, and rehabilitation of COM bring great socioeconomic burdens [8].…”
Section: Introductionmentioning
confidence: 99%
“…This study enrolled patients from the 1 million insurants in the Longitudinal Health Insurance Database (LHID), which comprises data derived from the National Health Insurance Research Database (NHIRD) for the period of 2000 to 2011. 23 , 24 The data in the NHIRD are derived from Taiwan's NHI program, which was implemented in 1995 and covers >98% of the population of Taiwan. The details in the LHID include the medical facilities where patients were enrolled, the types of medical services provided, and demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective cohort study used the beneficiary list of Longitudinal Health Insurance Database (LHID), with one million enrollees extracted from the National Health Insurance (NHI) Research Database (NHIRD) in the period of 2000-2011 (28)(29)(30)(31)(32)(33)(34). The Taiwan NHI program was set up in 1995, and it covers more than 98% of the total 23 million Taiwanese people.…”
Section: Data Sourcementioning
confidence: 99%
“…Pain Physician: March/April 2018; 21:E149-1E56 E150 www.painphysicianjournal.com sinus tracts (27). In our prior studies, we found that COM, a well-known chronic inflammatory disease, was associated with the risk of some cardiovascular diseases, such as ischemic stroke (28), hemorrhagic stroke (29), CAD (30), and atrial fibrillation (31), as well as a lot of neuropsychological disorders, e.g., dementia (32), depression (33), and epilepsy (34). Although COM is a rare disease, it is interesting to us to explore the correlation between COM and other diseases and to further imply the necessary disease prevention in the COM patients.…”
mentioning
confidence: 99%